(untitled) (Applied Biological Research, 2024)
The most prevalent protozoan that can infect a variety of animals, including birds and mammals, is Cryptosporidium. Certain species of Avian Cryptosporidium spp. are zoonotic and can cause fatal respiratory and digestive disorders in birds. Because they are in close proximity to humans, captive birds have the potential to serve as reservoirs. The current study reveals the molecular characteristics and prevalence of Cryptosporidium spp. from selected captive birds kept in district kasur. Fifty fresh fecal samples from captive birds belonging to three bird orders and five species were collected. To identify Cryptosporidium species, a polymerase chain reaction (PCR) technique that targets the small subunit 18S rRNA gene was employed. The prevalence rate of Cryptosporidium in captive birds was 6%. Of the three samples, Cryptosporidium baileyi 10% (1/10), Cryptosporidium meleagridis 5.5% (1/18) and Cryptosporidium parvum 10% (1/10). The rate of occurrence Cryptosporidium spp. infecting captive birds in Kasur having zoonotic potential is probably low. These findings provide baseline information to support future research on the genetic epidemiology and management of Cryptosporidium infection in avian species in Kasur